Extra levothyroxine dose in Ramadan maintained normal thyroid hormone levels in patients with hypothyroidism: a randomized controlled trial - Nawal Al-Mutawa; Bashair M. Mussa; Suhair Akhlaq; Zeenat AbdulWahid; Ahmad Qawas (Frontiers in Endocrinology)
IntroductionThe management of hypothyroidism during Ramadan represents a tangible challenge as levothyroxine (L-thyroxine), the first-line treatment for hypothyroidism, must be administered on an empty stomach at least 30 min before a meal in order to enhance its absorption.AimThe present study aimed to compare the thyroid-stimulating hormone (TSH) levels among patients with hypothyroidism treated with an extra dose of l-thyroxine (25 mcg L-thyroxine, treatment group) versus a standard/regular dose (1.6 mcg/kg) of l-thyroxine (control group) during the month of Ramadan.MethodsThis study is a randomized controlled clinical trial that included patients with hypothyroidism. Eligible participants (n = 103) were randomly allocated to the treatment group and the control group. Both groups attended five visits before, during, and after Ramadan. Several tests were conducted, including thyroid function, lipid profile, HbA1c, and vitamin D.ResultsOne of the most significant findings of the present study is that the extra dose of 25 mcg of L-thyroxine during Ramadan maintained the TSH levels of patients within the normal reference range, i.e., 0.55–4.78 mIU/L, at each visit during and after Ramadan without the need to wait 30 min before the meal. The mean TSH values were comparable between the treatment group and the control group during the five visits (visit 1, 3.00 ± 2.44 and 3.45 ± 3.02; visit 2, 3.62 ± 3.21 and 3.74 ± 2.74; visit 3, 4.19 ± 3.85 and 4.89 ± 2.92; visit 4, 3.54 ± 2.96 and 5.15 ± 4.26; and visit 5, 3.61 ± 3.05 and 3.32 ± 2.57, respectively).ConclusionThe present study demonstrated that the extra dose of L-thyroxine had a positive effect on keeping the TSH levels of patients in the normal reference range at each visit during and after Ramadan. However, in the control group, the mean TSH levels were higher than the normal range at visits 4 and 5.